Numerical simulation for condensation in the presence of noncondensable gas in the condenser with a multi-channel structure. (5th June 2022) - Zhang, Keyuan; Chi, Xiangyu; Nan, Zezhao; Li, Yaru; Wang, Naihua
Highlights: The condensation in the presence of NCG inside the PCCS condenser with a multi-channel structure is investigated. The NCG distribution in the PCCS condenser is predicted, and the formation reason is analyzed. The relationship between the condenser heat transfer performance and the NCG distribution is found. An optimal structure was presented, and the condenser heat transfer performance was evaluated. Abstract: Condensation in the presence of noncondensable gas is of interest to the passive containment cooling system in the nuclear power plant. Most researches focus on the heat transfer characteristics of condensation in an individual vertical tube or a parallel tube bundle. However, the influence of the condenser structure on condensation heat transfer is rarely considered in previous works. Thus, a numerical simulation was conducted for condensation in the presence of NCG in a condenser composed of two headers and 158 condenser tubes. A steady three-dimensional model was developed to predict the NCG distribution and the heat transfer performance of the condenser when the PCCS loop was stably running. The fluid inside the condenser was regarded as a single-phase mixture composed of steam and air, and the liquid film was evaluated by the Eulerian Wall Film model. The results indicated that the air tends to accumulate in the middle of the condenser tubes rather than the headers. The fluid flow in most of the tubes was blocked, so the heat transfer coefficients of pure steam and the steam-air mixture were lower than expected. An orifice plate was further designed to optimize the pressure and flow field in the PCCS condenser. The effect of the optimization was quantitatively evaluated. The results showed that the heat transfer performance of the condenser was improved by up to 87.8% with the orifice plate.